Reabilitação do sorriso com restaurações cerâmicas de diferentes espessuras cimentadas em diferentes substratos - Castro, Murilo Diniz de (2019)
The rehabilitation of the smile with ceramics aims to compensate for changes in shape, color and position of the teeth. The objective of this study is to report on the stages of planning and executing smile rehabilitation with ceramic restorations of different thicknesses cemented on different substrates. A female patient came to the dental consultation complaining about the aesthetics of the smile. On clinical examination, extensive restorations of unsatisfactory composite resin were observed. After radiographic and photographic examinations, and preparation of a study model, indirect lithium disilicate reinforced ceramic restorations were planned for elements 14 to 24. The restorative assay and wear guides were made based on the wax-up. Composite resin restorations were replaced and teeth were prepared for minimally invasive veneers (14, 13, 23 and 24), conventional veneers (21 and 22) and total crown (11 and 12). The restorations were made of lithium disilicate and the adaptation and color selection of the cement were checked. The internal surfaces of the restorations were treated and after application of the adhesive system, the cement was inserted into the restorations and they were positioned in the preparations. The excess cement was removed and each face was photoactivated for 40 seconds (1200mW/cm²). The contacts and occlusal guides were evaluated. In this way, it was possible to restore aesthetics and function, resulting in satisfaction of the patient and the execution team. It was concluded that careful planning and wellexecuted technique allow predictability in indirect restorations of different cemented thicknesses on different substrates.